−8 cm H2O, the new paradigm in chest drain management following thoracoscopic lung resection?. Issue 5 (30th March 2022) - Yaftian, Nima; Dunne, Benjamin; Ferrari, Isabelle; Antippa, Phillip
Abstract: Background: Chest drain suction of −20 cm H2 O has been used universally after lung resection. After introducing new guidelines, −8 cm H2 O was used routinely for all non‐pneumonectomy, thoracoscopic lung resections. We conducted a review to determine outcomes and safety. Methods: After introduction of the guidelines data were collected in the study institutions' thoracic surgical database and subsequently analysed. Results: A total of 155 patients underwent thoracoscopic lung resection. Mean patient age was 61.5 ± 13.6 years. Video‐assisted thoracoscopic surgery was performed in 92.2% (144/155) of patients and robotically‐assisted thoracoscopic surgery was performed in 7.8% (12/155) of patients. Lobectomy was performed in 56.8% (88/155) of patients, segmentectomy was performed in 11.6% (18/155) of patients and wedge resection was performed in 31.6% (49/155) of patients. Median ICC duration time was 1 day (IQR 1–3). Median length of stay was 3 days (IQR 2–6). For patients undergoing lobectomy median ICC time was 2 days (IQR 1–4.5) and median length of stay was 3.5 days (IQR 2–7), for segmentectomy median ICC time was 1 day (IQR 1–5) and median length of stay was 2 days (IQR 1–5) and for wedge resection median ICC time was 1 day (IQR 1–1) and median admission time was 2 days (IQR 1–4). Conclusion: A suction level −8 cm H2 O is safe to use for thoracoscopic lung resections from day 0 post‐operatively. A dedicated, prospective study comparing levels of suction should be performed. Abstract : Comparison of VATS lobectomy among multiple cohorts